Play Therapy Modified Ludo Games Decreasing Hyperactivity, Impulsivity, And Inattention In Children With Attention Deficit And Hiperactivity Disorder - Aniek Puspitosari (Poltekkes Kemenkes Surakarta, 2022)
Background: Attention Deficit and Hyperactivity Disorder (ADHD) is a disorder experienced by children with characteristics including hyperactivity, impulsiveness, and inattention things that affect the occupational performance of children in their activities. Occupational therapy play a role in handling ADHD children through play therapy methods. One of the children's games that have therapeutic value is the modified ludo game. Modified ludo game can be applied to decreasing symptom ADHD. The aim of the study was to investigate the effect of modified ludo game on hyperactivity, impulsivity and inattention in children with ADHD. Methods: Quantitative with pre-experimental research design, one group pretest-posttest with a sample size of 36 children with ADHD in RSUP Dr. Sardjito Yogjakarta. The sampling technique was purposive sampling, inclusion criteria: being able to understand simple commands, aged 3 - 6 years old, no motor impairment and able to move. The time of study was carried out in 2020-2021. Three rules modified ludo games models are provided in each session. The measuring instrument use ADHD rating scale that is valid and reliable. The data analysis method uses a paired sample t-test. Results: Paired sample t-test results showed that p-value < 0.05. Play therapy modified ludo games intervention have a possitive and significant effect on hyperactivity, impulsivity, and inattention in children with ADHD (ρ = 0.001). Conclusion: Play therapy modified ludo games has an effect on decreasing hyperactivity, impulsivity, and inattention in children with ADHD, so it’s recommended as an alternative game for occupational therapy for ADHD children.